Comet's nine lives - Brett, Jan, 1949- (New York : G.P. Putnam's, 1996)
Comet the cat uses up eight of his nine lives trying to find the right place to live on Nantucket Island.
School Library Journal
Publisher's Weekly
Booklist
4.2
K-3
Keywords: Cats -- Fiction; Nantucket Island (Mass.) -- Fiction; Cats -- Fiction; Nantucket Island (Mass.) -- Fiction